STRATEGI PENINGKATAN NILAI JUAL MAKANAN TRADISIONAL - Gumirlang Wicaksono; Raswan Udjang (Universitas Muhammadiyah Semarang, 2015)
The purposes of this study were to determine: (1). The strengths and weaknesses factors of SMEs in an effort to increase the sale value of traditional food products, (2). What strategies do SMEs need to increase the sale value of traditional food products, and (3). How is the performance of SMEs after the implementation of strategies to increase the sale value of traditional food products. The sample of this study was 20 members of the “Asosiasi KelompokTani Handayani” in Kepek Village, Wonosari, Gunungkidul, DIY. The method of collecting data in this study is observation and interview. The approach used in this research is qualitative descriptive method and action research. The stages in the action research include observation, implementation, and evaluation. The implemented program is education and training in thefield of packaging design, product labeling, the use of spinner machine, and the use of information technology facilities. Keywords: sale value of product, packaging, labeling, product quality